Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3399/bjgp18x699533
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients with a history of ovarian cancer for referral for genetic counselling: non-randomised comparison of two case-finding strategies in primary care

Abstract: BackgroundRecent guidelines recommend genetic counselling and DNA testing (GCT) for patients with ovarian cancer and survivors of ovarian cancer. Finding survivors of ovarian cancer is challenging. Detecting and referring them for GCT via primary care, to allow proper screening recommendations for patients and their family, may be a solution.AimTo compare the effectiveness and acceptance of two pilot strategies directed at case finding women with a history of ovarian cancer for referral for GCT by their GP.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…An additional five studies (17%) also showed improvements, though were not powered for significance [34,39,42,47,58]. Two studies had mixed results (e.g., improvements in some referral outcomes but not others) [3,40,59], while changes in referral rates could not be established in one study due to lack of historical comparator [60]. Five studies (16%) showed no significant improvement in referral [35,38,44,46,61].…”
Section: Study Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional five studies (17%) also showed improvements, though were not powered for significance [34,39,42,47,58]. Two studies had mixed results (e.g., improvements in some referral outcomes but not others) [3,40,59], while changes in referral rates could not be established in one study due to lack of historical comparator [60]. Five studies (16%) showed no significant improvement in referral [35,38,44,46,61].…”
Section: Study Outcomesmentioning
confidence: 99%
“…For example, in a study implementing a software program to facilitate assessment of familial cancer risk in general practice, only 14% of the practitioners surveyed had used the program at least once in the one-year study period (potentially explaining the lack of improvement in genetic referral rates) [38]. Clinicians varied in their beliefs about the appropriateness, acceptability and feasibility of interventions, for example clinicians in three studies [3,48,60] found the interventions too time-consuming for day-to-day use. Of the two studies reporting economic outcomes [38,62], these were expressed as marginal costs (e.g., unit costs associated with active intervention components, without reporting of costs to implement).…”
Section: Study Outcomesmentioning
confidence: 99%